Meningkatkan Sikap Nasionalisme Siswa dengan Model Contextual Teaching and Learning dalam Pembelajaran PPKN - Nurhayati, Tatik (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Nationalism is a very important thing for every Indonesian citizen, including students, because without a sense of Nationalism, a nation will lose its identity. Without a sense of Nationalism a nation will never become a unified whole because they do not feel they belong to each other. Therefore, Nationalism is so important in the life of the nation and state. Problems caused by the low Nationalism Attitude of SMK Negeri 1 Tuban students, which is manifested in their actions, often occur, especially in class XI IL-1. Such as truancy, not respecting differences between friends in terms of religion, ethnicity and culture, looking down on one's own culture, being undisciplined, lack of mutual cooperation, often criticizing each other between students, and a series of problems caused by low attitudes. Nationalism for students. Based on the problems that occurred in class XI IL-1, it was decided to overcome the problem of the low Nationalism Attitude of students in class XI IL-1. The author tries to conduct classroom action research by applying the Contextual Teaching and Learning (CTL) learning model in teaching and learning activities on Civics subjects in class XI IL-1 SMK Negeri 1 Tuban. From the results of this classroom action research, positive results were obtained. In the first cycle, students who reached the minimum completeness criteria reached 88.69% of the total number of students, namely 36. While in the second cycle it reached 100%. This student's Nationalism Attitude Assessment uses observation/observation techniques. Thus, it can be concluded that the application of the Contextual Teaching And Learning learning model in Civics learning can help in instilling the Nationalism Attitude in class XI IL-1 students of SMK Negeri 1 Tuban in the odd semester of the 2018/2019 academic year.